Hanging Noncalculous Gallbladder - Tzardinoglou, E. (Hindawi Publishing Corporation, 1996)
The removal of acalculous and not acutely inflamed gall-bladder in patients with typical biliary pain remains a questionable procedure. This study was conducted to present our experience. In the period 1982- 90, 1089 cases of calculous and acalculous gallbladder disease were treated in our clinic. In this period, 27 patients were subjected to cholecystectomy because of an acalculous, non inflamed gallbladder which was elongated lying in an abnormal position with a long cystic duct. The mean duration ofsymptoms supportive of cholelithiasis, was 5 years. Oral cholecystogram and ultrasonography led to the diagnosis and other causes ofchronic abdominal pain were excluded. There were 13 lumbar, 9 pelvic and 5 iliac gallbladders, with poor function in 20 of them. During cholecystectomy, the organ was invested by peritoneum and suspended in 7 cases from a mesentery. On pathological examination mild chronic inflammation was reported in 19 cases and minimal changes in 8. The minimum follow up was one year and the maximum 9 years. Complete relief of symptoms was achieved in all the cases. In conclusion, cholecystectomy should be offered in these symptomatic "hanging" gallbladders.